"Corynebacterium urinapleomorphum" sp. nov., isolated from a urine sample of a 2-month-old boy affected by rotavirus gastroenteritis. (January 2017) - Morand, A.; Chabrol, B.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We report the main characteristics of " Corynebacterium urinapleomorphum " strain Marseille-P2799 T (CSURP2799), isolated from a urine sample from a 2-month-old boy with rotavirus gastroenteritis.